"I slipped into the pages of a book": intertextuality and literary solidarities in South African writing about London. Issue 3 (3rd July 2018) - Thorpe, Andrea
Abstract: In this article, I argue that London plays a dual role in South African writing, as a "real" city at a particular moment in history, and as a textual, imaginative space. For many South African writers, London comes to stand metonymically for English culture and literature even if their attitude toward Englishness and Empire may be one of ambivalent critique. The intertexts invoked in South African representations of London forge literary solidarities, and foreground belated postcolonial engagements with modernity that are significantly displaced from the "margin" to the "center" of modernism (and Empire) itself.